Morphogenesis Response of Leaf and Petiole Explant of Rootstock Apple (Malus sylvestris Mill.) to Auxin and Cytokinin - Nafika, Wirentyas; Munawarti, Aminatun (Biotropika: Journal of Tropical Biology, 2023)
Apple rootstock is a plant type used in grafting propagation. Research related to the response of morphogenesis in this plant has not been widely carried out. This study aims to examine the influence of auxin and cytokinin ratios on morphogenesis in leaf and petiole explants of rootstock apples, seeking optimal response modifications. A 2-factorial, completely randomized design (CRD) was utilized in the investigation, with variations in the types of explants and combinations of plant growth regulators (PGR) in the culture medium. There were 12 treatments with five repetitions. Explants of young apple leaf (third leaf) and petiole rootstock that had been sterilized and cut with a size of 5x5 mm for the leaf and 5 mm long for the petiole were inoculated into MS medium with cytokinin, BAP (1 ppm) combined with auxin, IBA (0, 0.1, 0.2, 0.3, 0.4, 0.5 ppm). Each culture bottle contains five explants. The results showed that the average leaf explant was capable of producing 34% callus. Meanwhile, petiole explants produced 4% callus. Callus began to form on leaf and petiole explants on the 26th and 42nd days after inoculation, respectively. Most calluses have a compact texture with green, yellowish-white, and brownish-green variations. The PGR combination with the highest percentage of callus production in leaf explants was BAP 1 ppm + IBA 0.4 ppm treatment, whereas the petiole was BAP 1 ppm + IBA 0.3 ppm treatment. Therefore, the combination of PGR with the best callus response in this study can be used as a reference in the development of apple tissue culture.